Britain's Dragonflies A Field Guide to the Damselflies and Dragonflies of Great Britain and Ireland - Fully Revised and Updated Fourth Edition - Smallshire, Dave; Swash, Andy (WILDGuides, 2018)
A fully revised, comprehensive photographic field guide to the dragonflies of Britain and IrelandBritain's Dragonflies is the only comprehensive photographic field guide to the damselflies and dragonflies of Great Britain and Ireland. Written by two of Britain's foremost Dragonfly experts, this fully revised and updated fourth edition features hundreds of stunning images and identification charts covering all 57 resident, migrant and former breeding species, and six potential vagrants. The book focuses on the identification of both adults and larvae, highlighting the key features. Detailed species profiles provide concise information on identification, distribution, flight periods, behaviour, habitat, status and conservation. Other sections cover biology; how to watch, photograph, record and monitor Dragonflies; conservation status and legislation; and introduced exotic species.This redesigned, updated and expanded edition features:Beautiful colour plates showing males, females, immatures and all colour forms for every speciesOver 500 stunning photographs, many of which are new, and more than 550 illustrationsUp-to-date species profiles and distribution mapsDetailed, easy-to-use identification charts for adults and larvae